2020
DOI: 10.1002/eji.201948502
|View full text |Cite
|
Sign up to set email alerts
|

Impaired proteolysis by SPPL2a causes CD74 fragment accumulation that can be recognized by anti‐CD74 autoantibodies in human ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is associated with autoantibody production to class II MHC‐associated invariant chain peptide, CD74/CLIP. In this study, we considered that anti‐CD74/CLIP autoantibodies present in sera from AS might recognize CD74 degradation products that accumulate upon deficiency of the enzyme signal peptide peptidase‐like 2A (SPPL2a). We analyzed monocytes from healthy controls ( n = 42), psoriatic arthritis ( n = 25), rheumatoid arthritis ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Although these data associate the humoral immune response against CD74 to pathogenic T-cell responses, the exact trigger for increased anti-CD74 antibody production in SpA patients remains to be determined. Alternatively, anti-CD74 antibodies could recognize CD74 degradation products, which accumulate at the cell surface following impaired proteolysis of its transmembrane portion, as shown in monocytes from ankylosing spondylitis patients (26). There are currently no studies directly supporting the role of anti-CD74 IgA in SpA pathogenesis, although it is crucial to understand whether these antibodies are mechanistically involved or merely mirror Th1-and Th17-skewed T-cell responses in SpA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although these data associate the humoral immune response against CD74 to pathogenic T-cell responses, the exact trigger for increased anti-CD74 antibody production in SpA patients remains to be determined. Alternatively, anti-CD74 antibodies could recognize CD74 degradation products, which accumulate at the cell surface following impaired proteolysis of its transmembrane portion, as shown in monocytes from ankylosing spondylitis patients (26). There are currently no studies directly supporting the role of anti-CD74 IgA in SpA pathogenesis, although it is crucial to understand whether these antibodies are mechanistically involved or merely mirror Th1-and Th17-skewed T-cell responses in SpA patients.…”
Section: Discussionmentioning
confidence: 99%
“…CD74 also represents the surface cellular receptor for the cytokine MIF [ 129 ]. Formation of these autoantibodies could be linked to the reduced activity of the enzyme signal peptide peptidase-like 2A (SPPL2A), which in turn may cause the accumulation of CD74 and its degradation products, thus inducing antibody production [ 130 ]. The role of these autoantibodies in axial-SpA is currently unknown, but those directed towards the CLIP part of the molecule could be used as serum biomarkers to disclose the disease in these patients.…”
Section: Role Of Adaptive Immunitymentioning
confidence: 99%
“…However, recently, van Kempen et al found that monocytes in a subset of AS patients exhibit a defect in the enzyme signal peptide peptidase-like 2A (SPPL2A) [121]. Reduced SPPL2A activity causes the accumulation of CD74 and CD74 degradation products, which are deposited on the surface membrane upon exposure to IFNγ stimulation [121]. These degradation products can be recognized by the anti-CD74 antibodies in patients' sera.…”
Section: Antibodies Directed Against Intracellular Molecules Involved...mentioning
confidence: 99%